Inhibition and Activation of Bacterial Luciferase Synthesis - Eberhard, Anatol (1972)
Luciferase synthesis is repressed when bioluminescent bacteria are inoculated into fresh medium but is induced after the cells have grown in the medium for some time. In minimal medium, an activator which leads to induction of the enzyme is released into the medium by the bacteria. Complete medium contains a dialyzable and quite stable inhibitor which leads to repression of luciferase. The bacteria remove the inhibitor from the medium and also produce activator, thus allowing synthesis of the enzyme. Two unidentified nonluminescent strains of bacteria were unable to remove the inhibitor. Two different bioluminescent strains, Photobacterium fischeri and P. fischeri strain MAV, produce specific activators that are ineffective with cells of the other strain. The two activators are different with respect to heat stability, but both are small molecules. The activators can be assayed on the basis of their ability to counteract the inhibitor. Identification of the inhibitor and the activators may allow the bioluminescent system to be linked to other metabolic processes of the cells.